Pool boiling performance of HFE-7100 on hierarchically structured surfaces - dos Santos Filho, Erivelto; Kiyomura, Igor Seicho [UNESP]; Alves de Andrade, Bruno [UNESP]; Cardoso, Elaine Maria [UNESP] (Elsevier, 2021)
The evolution of the processes for modifying/manufacturing surfaces has facilitated the advancement in pool boiling research with surfaces capable of increasing the heat transfer coefficient (HTC) and the critical heat flux (CHF) through micro/nanostructures heating surfaces. The hybrid processes, which associate the removal or addition of material for the formation of microstructures followed by the addition of material for nanostructure formation, combine the benefits achieved with different intensification techniques in search of superior performance in boiling heat transfer. The thermal performance of pool boiling on surfaces with a combination of microfins and nanostructured surfaces, through nanoparticle deposition, was studied by using HFE-7100 at saturated conditions. The microtextured surfaces were nanostructured by boiling alumina nanofluid with 0.0007 vol%, applying a fixed heat flux of 500 kW/m2. The experimental boiling tests on hierarchical surfaces indicate a significant enhancement in the HTC (up to 65% compared to the microtextured surfaces) due to improved density of nucleation site and vapor bubble dynamics. The maximum heat flux corresponds to the maximum experimental heat transfer coefficient; the nanoparticle deposition on microtextured surfaces enhances the liquid absorption capacity, improving the surface's rewetting and delaying the dryout occurrence.
Keywords: Heat transfer performance; Hierarchically structured surfaces; Maximum heat flux; Pool boiling